Haptoglobin 2-2 phenotype is a risk factor for type 2 diabetes in Ghana - Quaye, I.K.; Ababio, G.; Amoah, A.G. (Journal of Atherosclerosis and Thrombosis, 2006)
We have investigated the role of haptoglobin gene polymorphisms in 129 type 2 diabetic patients and 87 non-diabetic subjects, classified by the ADA criteria, in Ghana. The diabetic subjects were recruited consecutively from the National Diabetic Management and Research Center of the University of Ghana Medical School, Korle-Bu, Accra, Ghana and were categorized by their haptoglobin phenotypes. The haptoglobin 2 allele was determined to be a risk factor for type 2 diabetes in Ghana (OR- 6.1, 95% CI - 1.8-21.2; P =.0.001) while the Hp1 allele appeared protective (OR = 0.56, 95% CI = 0.31-1.0; P =.06). The deleterious role of the Hp2 allele was further evidenced by the reduced risk associated with Hp2-1M mutant heterozygotes, who produce less Hp2 protein than the normal Hp2-1 heterozygote. (OR = 0.52, 95% CI = 0.27-1.0; P = 0.06). The subjects with the homozygous Hp2 allele were also hypertensive and overweight. There was no difference (p> 0.05) in the levels of triglycerides, total cholesterol, LDL and HDL between diabetic subjects with different haptoglobin phenotypes. We conclude that hypertensive and overweight individuals with the Hp2-2 phenotype in Ghana are at a high risk of developing type 2 diabetes and may require a more aggressive management.
Keywords: Diabetes; Ghana; Haptoglobin